Lessons learnt from two decades of graduate tracer research: Recommendations for the South African context - Senekal, J.; Munro, N. (South African Journal of Higher Education, 2019)
Graduate tracer studies may be an appropriate research method for responding to various problems in the South African higher education context, including difficulties associated with higher education transformation and graduate employability. However, there is little context-relevant literature on the implementation of the various methodologies that may be used, and no assessment of the relevance of these methods for the South African context. In an attempt to synthesise graduate tracer study research, and to recommend potential models for conducting graduate tracer studies in South Africa, a systematic quantitative literature review was conducted of 23 graduate tracer studies from 13 countries, published between 1995 and 2016. The findings from this review point to three potential models for implementation in the South African context: a large-scale model, a smaller-scale model, and a mixed-method model. These recommended models may allow for the more efficient and effective implementation of graduate tracer studies across the South African context.